Group Intervention with Aggressive Children and Youth Through Bibliotherapy. Issue 1 (2nd January 2017) - Shechtman, Zipora
ABSTRACT: Aggression in the school is one of the most disturbing behaviors that teachers and students face. It is usually addressed through preventive treatments, leaving the highly aggressive students unaffected. Group psychotherapy is a viable method to treat aggressive youth, despite reservations raised in the professional literature, when therapy is adjusted to this unique population. Aggressive children and youth are quite resistant to change, thus, creative methods are needed to engage them in therapy. This article suggests an innovative intervention, using bibliotherapy as an adjunct to an integrative theory of treatment, adjusted to the specific characteristics of aggressive children. The article describes the intervention, its theoretical foundation, and provides wide evidence for its effectiveness with aggressive children and youth.